Deletions of the elastin gene at 7q11.23 occur in approximately 90% of patients with Williams syndrome. - Nickerson, E (1995)
To investigate the frequency of deletions of the elastin gene in patients with Williams syndrome (WS), we screened 44 patients by both FISH and PCR amplification of a dinucleotide repeat polymorphism. FISH was performed using cosmids containing either the 5' or the 3' end of the elastin gene. PCR analysis was performed on the patients and their parents with a (CA)n repeat polymorphism found in intron 17 of the elastin locus. Of the 44 patients screened, 91% were shown to be deleted by FISH. Using the DNA polymorphism, both maternally (39%) and paternally (61%) derived deletions were found. Four patients were not deleted for elastin but have clinical features of WS. Since deletions of elastin cannot account for several features found in WS, these patients will be valuable in further delineation of the critical region responsible for the WS phenotype. Although PCR can be useful for determining the parental origin of the deletion, our results demonstrate that FISH analysis of the elastin locus provides a more rapid and informative test to confirm a clinical diagnosis of WS. The presence of two copies of the elastin locus in a patient does not, however, rule out WS as a diagnosis.